1982
DOI: 10.1002/ana.410120414
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral dystrophy associated with hearing loss and coats syndrome

Abstract: Two unrelated cases of infantile facioscapulohumeral dystrophy (FSHD) with Coats syndrome of the retina and sensorineural hearing loss are described. Children with otherwise unexplained visual or hearing deficit should be examined for somatic muscle weakness, which may present only as facial weakness. Early recognition of Coats syndrome in children with FSHD may lead to preservation of vision with appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 13 publications
3
18
1
Order By: Relevance
“…Six of 11 patients in the Carroll and Brooke (1979) group also had sensorineural deafness, as had most of our patients. None of our patients had visual difficulties due to retinal telangiectasia as described by Small et al (1968), Taylor et al (1982), Wulff et al (1982), Fitzsimons et al (1987), and Yasukohchi et al (1988).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Six of 11 patients in the Carroll and Brooke (1979) group also had sensorineural deafness, as had most of our patients. None of our patients had visual difficulties due to retinal telangiectasia as described by Small et al (1968), Taylor et al (1982), Wulff et al (1982), Fitzsimons et al (1987), and Yasukohchi et al (1988).…”
Section: Discussionsupporting
confidence: 59%
“…These findings are compatible with autosomal dominant transmission with variable expressivity in some families. On the other hand, IFSH MD occurring in sibships without apparent muscle disease in the parents has been reported by Small (1968) and by Yasukohchi et al (1988), and sporadic cases have been reported by others (Hanson and Rowland 1971, Taylor et al 1982, Matsuzaka et al 1986). It is possible that there is an autosomal recessive form of IFSH MD.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Two papositivity. Others also reported normal BAEP findings tients showed a significant I-V ÎW D (0,41-0.53 ms), ¡n FSHD (12,14,18). The finding of a decreased I-V which was a bilateral finding in 1, and a (unilateral) interval in 2 patients with severe hearing loss ( 10) would IM-V ÍWD (0.27-0.37 ms) was found in 2 patients.…”
Section: Discussionmentioning
confidence: 92%
“…The FSHD gene has been mapped to chrom o some 4 (4). Associated findings are hearing loss (5 -11) or hearing loss, Coats' disease and mental retardation in various combinations (12)(13)(14)(15)(16)(17)(18). Sen sorineural hearing loss (SNHL) may be associated with vestibular and oculomotor impairment in neuro muscular disease (19); we therefore investigated the auditory, vestibular and oculomotor systems in FSHD patients.…”
Section: Vestibular Systemmentioning
confidence: 99%